DEVELOPMENT OF THE BALLISTIC EFFICIENCY OF JAVELIN THROWERS - Muxammadjonov Muslimbek Muxsinjon о‘g‘li (Proximus Journal Publishing, 2024)
Undoubtedly, today in world sports there is an increase in irreconcilable disputes, and accordingly, the training of athletes is built on a certain system and creates an image compatible with science. Although the athletes of our country have achieved certain achievements in the world arenas in javelin throwing, it is necessary to develop training structure programs in order to maintain these indicators and achieve new results. In the course of the current competition, it is necessary to achieve high sports results based on the improvement of the necessary abilities in the system of training athletes in javelin throwing. For this, it is necessary to further develop the ballistic performance of javelin throwers. This is one of the urgent tasks that must be solved today in the system of training athletes
Keywords: training; increase; irreconcilable